Kromoblastomikosis Penyakit Jamur yang Terabaikan - Danu Yuliarto; Achmad Satya Negara; Harijono Kariosentono; Nugrohoaji Dharmawan; Nurrachmat Mulianto (MEDICINUS, 2023)
Chromoblastomycosis is a deep fungal infection of the skin and subcutaneous tissue caused by pigmented or dematiaceous fungi. This disease is endemic in tropical and subtropical regions such as Asia, Africa, and Latin America. Chromoblastomycosis is more common in adult men who work in agricultural areas, work as gardeners, or as carpenters. The diagnosis of chromoblastomycosis is confirmed by the finding of muriform cells or medlar bodies obtained from skin scrapings, microscopic culture, or tissue histopathological examination. The clinical feature varies, the initial lesion is a papule that spreads slowly over several months or years, and then this lesion will form a plaque with atrophic center. Many patients go undiagnosed at the early stage of the disease because this stage is rarely seen. Treatment of chromoblastomycosis includes surgery for the initial lesion and pharmacological therapy using antifungal agent such as itraconazole, the most commonly used drug for the treatment of chromoblastomycosis. The prognosis for chromoblastomycosis is poor, except on new lesions.